The Influence of Social Deixis in Students’ Conversation - Savyanandaru, Oki; Yuliasri, Issy (Universitas Negeri Semarang, 2017)
In this study, we focused on the influence of social deixis on maintaining the level of politeness. The subject of this study was about speaking classroom activity of the eleventh year students of SMA N 3 Semarang. We intended to prove that social deixis influences the level of politeness and describe what factors influence it. This type of study was qualitative research since we did not collect the numerical data. The data was collected in the form of sentences. Research Method used in this study was a discourse study. In this study, we used the ethnography of communication approach since this study talked about social relation between people. In this study, the students were asked to use the social deixis and the level of politeness appropriately. Furthermore, there were observations, questionnaire and interview as this research instruments. The findings of the study showed that there were three factors that influenced social deixis on maintaining the level of politeness based on the students’ conversation. Those were social rank, social distance and formality.